Caracterización de híbridos interespecíficos de papa diploide (Solanum spp.) para su uso en cruzamientos 4x – 2x - Quispe, J.L. (Universidad Nacional Agraria la Molina, 2011)
Wild diploid species of Solanum constitute a major germplasm pool for introducing resistances in tetraploid potato. Following a 4x-2x breeding scheme, 166 diploid late blight resistant genotypes, offspring from crosses among series Piurana (S. piurae, S. paucissectum and S. chiquidenum) and Tuberosa (S. cajamarquense), and diploid potato cultivars (S. phureja, S. goniocalyx and S stenotomum), were selected as the starting material for this study. The study evaluated the resistant hybrids both individually and grouped, according to their pedigree, choosing the best among them to continue with the 4x-2x late blight resistance breeding scheme. For fulfilling this objective, assurance was needed regarding the hybridity of the samples. The methodology we used was SSR molecular markers. This test confirmed the pedigree of most samples essayed. Eight samples presented foreign alleles, which is an indication that they could not be a product of the cross they are supposed to be. Afterwards, we ascertained the ploidy level of the plants by chloroplast counting, flow cytometry and direct chromosome counting. Using these techniques, we were able to compare the results obtained: Ploidy number was diploid in all samples evaluated, as expected from the crossing of two diploids. Flow cytometry proved to be a very reliable technique, relaying results similar as the ones obtained through chromosome counting. Chloroplast counting accurately identified more than 95 percent of the evaluated samples. For the next step, we conducted a morphological characterization of each individual genotype and family in order to trace each plant along the breeding scheme. We also evaluated certain characteristics of agronomic importance to reduce the time from introduction of the resistance to obtaining an economically viable variety. The characteristics of stolon length, tuber uniformity, proportion of tubers with sprouts, shape of tuber and eye deepness contributed to the selection of twelve genotypes with the best agronomical characteristics, allowing focus to be placed on the best individuals. Finally, we evaluated the pollen's fertility and ability to produce unreduced pollen of these hybrids. Being that the aim of the breeding scheme was to transfer the resistance from diploid wild potatoes to the tetraploid gene pool, production of unreduced pollen was one of the major factors in selecting the best hybrids for breeding. Despite the fact that they are not the best when taking their agronomical traits into account, the eight genotypes with more than 0.5 percent of unreduced pollen found by this study would be the ones recommended as male parents for direct crosses to tetraploid germplasm.